Case Study : Smilling Orchid Bakery and Cake / Nur Farah Izzati Nawi - Nawi, Nur Farah Izzati (2021)
Regarding to fulfil Fundamental of Entreprenurship course requirement, I need to carry out a case study. In a case study, I need to collect all information about a company to complete a study case, so I decided to contact the manager of Smilling Orchid Bakery & cake who is Mister Alia Zainal which is manager of the company to do some of interview session with me. At the end of the case study, we managed to get a lot of new knowledge about businesses in the real world. Smiling Orchid Bakery & Cake are business that sells cakes and pastry in Tanah Merah, Kelantan. During the interview session with manager of smilling orchid Bakery & cake, we have know many information about the company which is the owner of this company is Mr So Yu Cheng. Therefore, we also know the location of this company at 473, Jalan Dato Nik Mustapha 17500, Tanah Merah, Kelantan. While their factory address at Lot 6750, Jalan Jedok 17500, Tanah Merah, Kelantan. The business’s main competitor is Secret Recipe who is a household name in the bakery industry. The business make up the competition by selling their products at a more affordable price for all the community. The company also promote their business and products through advertisement in the Social Media such as Facebook where they updates any discounts and promotion to their customers. The company’s vision is they aim to create a new product every year so that their customer’s would not be bored of the same products. Their mission is to create a bakery that will provide best quality baked goods on site and also providing training classes to those interested to learn cake and pastry baking. They wish to be a well known pastry shop in Kelantan. Smiling Orchid Bakery and Cake expects to catch the interest of regular loyal customer base with its special variety of bun and cakes. This company plans to build a strong market position in the town, due to the mild competitive climate in the area. Smiling Orchid Bakery and Cake aims to offer its product at a competitive price to meet the demand of the middle-to higher-income local market area residents. This bakery is fully owned by Mr. So Yu Cheng. He hired a total of 10 employees (including cafe and factory) and also always welcoming part timer to work at his bakery, cafe and factory. In term of products, this bakery provides freshly prepared bakery and pastry products at all times during business operations. Four to six moderate batches of bakery products are prepared during the day to assure fresh baked goods are always available.